Putting Quantitative Models to the Test: An Application to the U.S.-China Trade War - Rodrigo Adão; Arnaud Costinot; Dave Donaldson (The Quarterly Journal of Economics, 2025)
Abstract The primary motivation behind quantitative work in international trade and many other fields is to shed light on the economic consequences of policy changes and other shocks. To help assess and potentially strengthen the credibility of such quantitative predictions, we introduce an IV-based goodness-of-fit measure that provides the basis for testing causal predictions in arbitrary general equilibrium environments as well as for estimating the average misspecification in these predictions. As an illustration of how to use the measure in practice, we revisit the welfare consequences of the U.S.-China trade war predicted by Fajgelbaum et al. (2020).